Factors associated with complementary feeding practices among children aged 6-23 months in Indonesia - Esti Yunitasari; Ahmad Hisyam Al Faisal; Ferry Efendi; Tiyas Kusumaningrum; Fildzah Cindra Yunita; Mei Chan Chong (BMC, 2022)
Abstract Background Complementary foods with breastfeeding are foods or drinks given to children aged 6-23 months to meet their nutritional needs. The non-optimal provision of complementary feeding influences malnutrition in children of this age. Aims To analyze the factors associated with complementary feeding practices among children aged 6-23 months in Indonesia. Methods A cross-sectional design was employed using data from the 2017 Indonesia Demographic and Health Survey. A total of 502,800 mothers with children aged 6-23 months were recruited through multistage cluster sampling. Data were analyzed using a logistic regression test to determine the correlation between predisposing, enabling, and reinforcing factors and complementary feeding practices. Results A prevalence values of analysis showed that approximately 71.14%, 53.95%, and 28.13% of the children met MMF, MMD, and MAD, respectively. The probability of achieving minimum dietary diversity (MDD) was high in the following: children aged 18-23 months (odds ratio [OR] = 9.58; 95% confidence interval [CI] = 7.29-12.58), children of mothers with higher education (OR = 5.95; 95% CI = 2.17-16.34), children from households with upper wealth index (OR = 2.53; 95% CI = 1.85-3.48), children of mothers who received childbirth assistance by professionals (OR = 1.63; 95% CI = 1.20-2.20), and children of mothers who had access to the Internet (OR = 1.26; 95% CI = 1.06-1.50). Moreover, children from households with the upper wealth index (OR = 1.40; 95% CI = 1.03-1.91), children whose mothers were employed (OR = 1.19; 95% CI = 1.02-1.39) living in urban areas (OR = 1.28; 95% CI = 1.06-1.54) and children of mothers who received childbirth assistance by professionals (OR = 1.33; 95% CI = 0.98-1.82) were more likely to meet Minimum Meal Frequency (MMF). Finally, children aged 18-23 months (OR = 2.40; 95% CI = 1.81-3.17), of mothers with higher education (OR = 3.15; 95% CI = 0.94-10.60), from households with upper wealth index (OR = 1.41; 95% CI = 1.05-2.90) and born with professional childbirth assistance (OR = 1.82; 95% CI = 1.21-2.75) were significantly associated with minimum acceptable diet (MAD). Conclusions The findings revealed that the prevalence of MDD and MAD in Indonesia was low. Strategies such as improving health services, economic conditions, and education level of mothers are needed to improve infant and young child feeding in Indonesia.